Assessing Indigenous Community Sustainability Aspects in The Development of Coastal Tourism Areas - Dabamona, Samsudin Arifin; Salim, Mursalam (Universitas Pendidikan Indonesia, 2024)
ABSTRACTThe objective of this study is to gain insight into the perspectives of indigenous communities residing in three traditional villages regarding the growth of coastal tourism in Hamadi-Holtekamp Jayapura, Papua. Additionally, the study attempts to identify the elements contributing to the sustainability of these communities as a consequence of the tourism development. The study employed a theme analysis approach, combining two primary methods for data collection: individual semi-structured interviews and observation. The results reveal three main themes: coastal tourism and social responsibility, coastal tourism and environmental exploitation, and loss of cultural values. This study reveals the ways in which coastal tourism, although still offering beneficial prospects, can also pose obstacles to the long-term viability of indigenous communities. Various measures are proposed, such as actively considering and giving priority to the sustainable future of indigenous communities as a collective and fostering increased engagement and collaboration with them. Furthermore, the tourism industry and local governments need to position them as equal partners in the tourism industry and establish a tourism development concept that maintains the sustainability of the socio-cultural environment and establishes positive relationships with various parties to avoid conflicts within indigenous communities or outside indigenous communities.ABSTRAKPenelitian ini bertujuan untuk memahami persepsi masyarakat adat di tiga desa di Hamadi-Holtekamp, Jayapura, Papua, terhadap pertumbuhan pariwisata pesisir. Selain itu, penelitian ini mengidentifikasi faktor-faktor yang mempengaruhi keberlanjutan masyarakat adat dalam konteks pengembangan pariwisata. Melalui pendekatan analisis tematik dan pengumpulan data melalui wawancara mendalam dan observasi, penelitian ini mengungkap tiga tema utama: tanggung jawab sosial dalam pariwisata, eksploitasi lingkungan, dan pengikisan nilai-nilai budaya. Hasil penelitian menunjukkan bahwa pariwisata pesisir, meski membawa peluang ekonomi, juga menimbulkan tantangan bagi kelangsungan hidup masyarakat adat. Oleh karena itu, penelitian ini menyarankan pentingnya mempertimbangkan masa depan masyarakat adat secara berkelanjutan, meningkatkan partisipasi mereka dalam perencanaan pariwisata, serta membangun kemitraan yang setara antara industri pariwisata, pemerintah, dan masyarakat adat. Pendekatan ini diharapkan dapat mendorong pengembangan pariwisata yang berkelanjutan secara sosial, budaya, dan lingkungan, serta mencegah konflik di dalam dan luar komunitas adat.